Dodging expropriation? : The role of cash holdings as a firm-level driver of risky FDI location choices - King, Timothy; Loncan, Tiago; Khan, Zaheer (Elsevier, 2025)
Despite the higher expropriation risks associated with investing in corrupt countries, many multinational enterprises (MNEs) still choose to do so. The motivations for investing in such countries remain unclear. Using rich data on 3500 outward foreign direct investment (FDI) projects undertaken by U.S. manufacturing MNEs, we find that cash-rich firms are significantly less likely to locate FDI activities in more corrupt countries. We show that this effect is most pronounced in firms with stronger governance and monitoring regimes. Overall, our findings, which are robust to a battery of tests and treatment of a potential endogenous determination of cash holdings and FDI location decisions, suggest that liquidity influences firms’ perceived expropriation risk, with cash-rich firms optimally sheltering their FDI activities from more corrupt countries when expected expropriation costs outweigh the economic gains that can be easily exploited through FDI. These findings have important implications for research, practice, and policy regarding the FDI location decisions of MNEs.
Keywords: FDI Location; Cash Holdings; Corporate Governance; MNEs; Ownership; corruption; expropriation; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|